KAMUS ISTILAH GAMBELAN GAMBANG DESA JINENGDALEM KECAMATAN BULELENG KABUPATEN BULELENG BALI - I Made Susila Putra (Subasita: Jurnal Sastra Agama dan Pendidikan Bahasa Bali, 2020)
Gamelan Gambang is one of a traditional Balinese musics or gamelan karawitan which still exists and is generally used at Ngaben ceremony. In Jinengdalem village, this gamelan also has function to accompany Piodalan ceremony and death ceremony which is called Mabeya. The purpose of this research is finding, expressing and presenting the terms of Gamelan Gambang in dictionary form. Researcher was guided by morphological and lexicological theories to determine the structure and meaning of the terms of Gamelan Gambang, as well as the field of syntax in determining the categories, functions and roles of the term Gamelan Gambang in the sentence. This was a qualitative research. The results of this study are (1) The form of the term Gamelan Gambang can be known in 27 terms which get undergoing process of composition, 19 terms of Gamelan Gambang undergoing affixation process, 6 terms undergoing zero derivation process, and 2 terms of Gamelan Gambang undergoing reduplication process, (2) from the syntactic study, it can be seen that  there are totaling 46 lexicon of the term of Gamelan Gambang  as nomina (noun) category, for verb totaling 5 lexicon, and adverb totaling 7 lexicon. For the role of the term in Gamelan Gambang if it is applied to a sentence can be seen tha there are 9 lexicon acts as active word and 42 lexicon acts as passive word. The term of Gamelan Gambang which functions as subject is 3 lexicon, as predicate is 5 lexicon, as object is 41 lexicon, and as information is 7 lexicon, (3) from the Semantic study, the results of the lexical meaning of the Gamelan Gambang term has 4 lexicon synonym relations, a hyponym meaning 4 lexicon and a polysemic meaning 5 lexicon. In this Gamelan Gambang dictionary term, it is identified main entries in the form of basic words totaling 40 lexicon accompanied by invented words totaling 13 lexicon and phrases, clauses or examples in the form of sentences.Keywords: Gamelan Gambang, morphology, syntax, lexical meaning, structural meaning and dictionary.